(untitled) (Al-Qamar, 2025)
Pollutants from vehicles pose a direct threat to our ecosystem due to the emission of hazardous gases. The increasing urbanization of the world has led to higher consumption of petroleum products. These products, such as diesel and petrol, are derived from crude oil, which has limited reserves, and natural gas stocks are also limited. Countries with low or no fossil fuel reserves face significant shortages of gasoline, crude oil, and petroleum production and supplies. This study aims to evaluate the effects of using biodiesel as an additive in diesel engines for the analysis of carbon and particulate matter emissions. The results found that carbon emissions reduce 1.13% in biodiesel, 2.54% reduction in aluminum oxide and particulate matter emissions were 4.459 biodiesel 9.669% reduced in aluminum oxide with compared to diesel. Furthermore, the addition of nanoparticles to the biodiesel blend further reduced emissions.